Hydrolysis products of dibutyltin dichlorides - Chua, C.K.; Murray, J.D. (Royal Society of Chemistry, 1971)
The hydrolysis of di-s-butyltin dichloride yields similar products to those found for the di-n-butyl compound whereas the hydrolysis behaviour of di-t-butyltin dichloride is markedly different. Distannoxanes are not found in the latter case but instead di-t-butyltin hydroxide chloride is obtained. Under strongly basic conditions di-t-butyltin oxide is formed which has unusual structural properties and can easily be converted into a 'dihydroxide.' Comparative i.r. data derived from analogous systems are presented.